Variants and social interaction: A study of the Acehnese Daya Dialect - Teuku Alamsyah; Razali Razali; Teuku Munawar; Ramli Ramli (Universitas Syiah Kuala, 2024)
Every language has its varieties or dialects, including the Acehnese language, which includes the Daya dialect. This paper examines how the variants of the Acehnese Daya dialect are used in social interactions. The study employed a qualitative method, with primary data obtained from speakers of the Acehnese Daya dialect in each variant. Secondary data sources included literature on the Acehnese language and its variants, contributing to the interpretation of the primary data. Data collection involved observation and interviews, with data analysis conducted using the interactive model analysis, which includes four stages: data reduction, data categorization, data presentation, and conclusion. The study reveals that the Acehnese Daya dialect, as a variety of Acehnese, can be distinguished as the Meulon and the Meuke languages. The Meulon dialect does not have variants, while the Meuke dialect has two variants characterized by phonetic differences: bune, mane, jine, lake, and bunai, manai, jinai, and lakai, which mean earlier, taking a bath, now, and husband, respectively. Each variant also exhibits some phonetic, lexical, and semantic similarities. Unique lexical resources in the Acehnese Daya dialect are another distinguishing feature compared to general Acehnese. Code-switching and code-mixing between variants are also found in the speech of Acehnese Daya dialect speakers. The distinctiveness of the Acehnese Daya dialect, particularly its variants, emphasizes the importance of preserving linguistic diversity within communities.